1991
DOI: 10.1002/ajim.4700190305
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos‐related disease in public school custodians

Abstract: A cross-sectional prevalence study of 120 public school custodians was carried out. The purposes were 1) to investigate the prevalence of asbestos-related disease in a group of custodians at risk for asbestos exposure in public schools and 2) to determine the proportion with disease attributable to exposures in school buildings. Medical and occupational histories, flow-volume loops, and posterior-anterior, lateral, and anterior oblique (AO) chest radiographs were obtained. Single breath DLCO was measured and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…school custodians) have been 'highly' exposed and are now predisposed to developing asbestosis related dis eases in the future [7,[34][35][36] are important factors that should be considered when evaluating cost. This is most evident when the synergistic effects of asbestos exposure and smoking are evaluated in association with the high percentage of cigarette smokers consistently reported in surveys of asbestos abatement workers [11,37,38].…”
Section: Methods and Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…school custodians) have been 'highly' exposed and are now predisposed to developing asbestosis related dis eases in the future [7,[34][35][36] are important factors that should be considered when evaluating cost. This is most evident when the synergistic effects of asbestos exposure and smoking are evaluated in association with the high percentage of cigarette smokers consistently reported in surveys of asbestos abatement workers [11,37,38].…”
Section: Methods and Site Descriptionmentioning
confidence: 99%
“…This industry has developed as a result of various reports about the occupational envi ronment, of diseases associated with exposure to airborne asbestos [6][7][8][9][10][11][12][13][14][15][16][17] and a public concern of exposure to nonoccupationally related populations [18,19]. Regulations have been enacted that require engineering controls, no tification to regulatory agencies and protective practices for occupationally exposed personnel and for public health protection [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have suggested that the risk from some exposure to asbestos, especially for schoolchildren, is extremely low and these extreme activities and cost expenditure for abatement are not warranted [4,[18][19][20]. Certainly the estimates of risk do not apply equally to all persons exposed to asbestos and other studies have suggested that workers in a variety of jobs may experience greater exposure to airborne asbestos than those performing asbestos abatement [21,22]. It has been suggested that higher concentrations of asbestos may exist in the air after abatement is completed than before abatement [4,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that asbestos, a well-established carcinogen, has been used extensively in industry and households makes it an important health concern. It has been suggested that the danger of developing asbestos-related diseases extends beyond that of a simple occupational hazard because it has been documented in family members of asbestos workers, in individuals living in the neighborhood of industrial sources of asbestos, and in some schools and public buildings where asbestos is being used as insulation material (3)(4)(5). Moreover, resuspension of materials from asbestos-containing ceilings has been shown to be the main source of asbestos pollution in old, poorly maintained buildings (6).…”
mentioning
confidence: 99%